2022
DOI: 10.3390/antibiotics11020149
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal Endemicity of Carbapenemase-Producing Klebsiella pneumoniae in ICUs of a Greek Tertiary Care Hospital

Abstract: Carbapenemase-producing Klebsiella pneumoniae (CPKP) emerged in Greece in 2002 and became endemic thereafter. Driven by a notable variability in the phenotypic testing results for carbapenemase production in K. pneumoniae isolates from the intensive care units (ICUs) of our hospital, we performed a study to assess the molecular epidemiology of CPKP isolated between 2016 and 2019 using pulse-field gel electrophoresis (PFGE) including isolates recovered from 165 single patients. We investigated the molecular rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Another study conducted in Iran analyzed 165 K. pneumoniae strains isolated from different samples; their PFGE analysis showed 17 clusters with an 80% similarity rate. (32) In this study, the genetic diversity among isolates was high; one reason for this could be the diversity of sample sources and because our samples were fewmany from diverse sources.…”
Section: Discussionmentioning
confidence: 85%
“…Another study conducted in Iran analyzed 165 K. pneumoniae strains isolated from different samples; their PFGE analysis showed 17 clusters with an 80% similarity rate. (32) In this study, the genetic diversity among isolates was high; one reason for this could be the diversity of sample sources and because our samples were fewmany from diverse sources.…”
Section: Discussionmentioning
confidence: 85%
“…All isolates were tested phenotypically for the detection of MBL, KPC, or both carbapenemase categories using the meropenem disc test. Based on our hospital’s epidemiology, MBL-positive K. pneumoniae were considered as probable VIM or NDM producers [ 32 ]. Therefore, MBL-positive K. pneumoniae isolates were further tested with the modified Hodge test [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, in Greece, the most common carbapenem-resistant microorganism is K. pneumoniae , with most strains being KPC producers. However, non-carbapenemase mechanisms are also common, and certain studies have demonstrated that double carbapenemase production (e.g., KPC + VIM) can be encountered in up to 25% of isolates [ 121 , 122 , 123 ]. OXA-type carbapenemase production is uncommon in non- Acinetobacter cases, with rare isolations of K. pneumoniae strains co-expressing OXA-48-like enzymes in addition to other carbapenemases [ 122 ].…”
Section: Carbapenemase Detection—rational Testing and Treatment Optio...mentioning
confidence: 99%
“…However, non-carbapenemase mechanisms are also common, and certain studies have demonstrated that double carbapenemase production (e.g., KPC + VIM) can be encountered in up to 25% of isolates [ 121 , 122 , 123 ]. OXA-type carbapenemase production is uncommon in non- Acinetobacter cases, with rare isolations of K. pneumoniae strains co-expressing OXA-48-like enzymes in addition to other carbapenemases [ 122 ]. Epidemiological data regarding the resistance phenotypes of other carbapenem-resistant Gram-negative bacteria such as E. coli are missing, but no double carbapenemase production has been reported.…”
Section: Carbapenemase Detection—rational Testing and Treatment Optio...mentioning
confidence: 99%